Η επίδραση του 1-μεθυλοκυκλοπροπενίου στη μετασυλλεκτική συμπεριφορά καρπών λεμονιάς (ποικ. λαπήθου) κατά τη μεταφορά τους σε μακρινές αγορές - Σισμανίδης, Γεώργιος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Lemons are one of the most important citrus fruit of high nutritional value. Lemon, due to the climatic conditions required for its growth, grown in specific parts of the world. The fact that has prompted the lemon trade to meet the high demand of the market. The fruits harvested when the outer part of the fruit is still green, but mature. This practice followed by producers, taking advantage of the lack of lemons on the market, for making more profit from their sale. The maturity of the fruit's interior does not keep pace with the color change of the outer part. However, consumers associate the maturity of the fruit with the color of the outer part, having the tendency to buy lemons with bright yellow color. In consequence, the citrus industry has developed the practice of degreening, using ethylene. The process of degreening is employed to promote external color development meeting the consumers’ demands. Despite the commercial beneficial effect of ethylene on color development, its use significantly reduces the post-harvest life of the fruit, stimulating senescence and rendering fruit more susceptible to postharvest decay and peel disorders. The discovery of 1-methylcyclopropene (1-MCP), a substance that competes with ethylene for it is binding to ethylene receptors, significantly reduced its activity, was considered by the research community as a candidate for inhibiting the negative effects of ethylene on fruit citrus fruit. The purpose of this work was to study the effect of 1-MCP in postharvest behavior of the lemon fruit (cv. Lapithos) during transport to distant markets, determine the quality characteristics of the fruit during shelf life and manage the negative effects of degreening, after cold storage of the fruits for 30 days. The novelty of this study lies in the fact that it took place on an industrial scale in real- life conditions, trying to simulate the fruit shipping conditions during transport to distant markets. In the current study, the lemon fruits harvested at the stage of commercial maturity bearing green color and then followed the process of degreening. The fruit treated with ethylene 2mL L-1 for 72 h at 23-25oC, and relative humidity 90-95%. After degreening process had fully or partially yellow fruits. Additionally, green fruits also used, which are not presented in the degreening process. Subsequently, fruit treated with 1-MCP 900μL.L-1at 6oC for 24 h and afterwards the fruit washed, dipped in fungicide, wax and sorted, selecting only the well- formed. Subsequently, fruits were stored at 2°C (''quarantine measure'') and 6oC for 30 days. Finally, they divided into 12 treatments; each treatment unit included 120 lemons fruit having representative and uniform size. Fruit were analyzed for juice content, weight loss, soluble sugars content (SSC), titratable acidity (TA), ripeness index (RI), technological index (TI), color index, incidence of post-harvest decay and the appearance of chilling injury (CI) symptoms at harvest, after 30 days of cold storage and after maintenance at 20oC (shelf life)for a 7 days. According to the experimental data, it was observed that the juice content increased significantly during the shelf life in all treatments. Furthermore, the yellow fruit that treated with 1-MCP and wax presented significantly lower juice content compared to those of control. Likewise, a significant increase in weight loss observed during the shelf life in all treatments. Nevertheless, the fruit treated with wax presented slightly lower weight loss than controls. The use of 1-MCP had not significant effect on weight loss since the 1-MCP treated fruit did not differ from control. Data revealed that the SSC and TA of the fruit slightly increased during the shelf life because of its condensation due to weight loss. 1-MCP did not affect the SSC, TA and RI whereas 1-MCP- treated fruit presented lower TI values than control mostly due to decreased juice content they showed up. Furthermore, the most profound effect of 1-MCP observed in color index where the 1-MCP-treatedfruit presented higher values of L*, a*, h*and lower values of b* and C* compared to controls. As a result, it can be said therefore that the 1-MCP block both the chlorophyll destruction and carotenoid biosynthesis stopping the ‘carry-over effect’ of ethylene which continues shortly afterwards the process of degreening. The combination of 1-MCP and wax presented stronger effect in all color indexes. Finally, a few 1-MCP-treatedfruit presented slightly higher percentage of post-harvest decay and CI symptoms. However, the fact that cannot be attributed confidently to the action of 1-MCP. In summary, the use of 1-MCP did not show significant results in postharvest behavior of the lemon fruit. Specifically, 1-MCP-treated fruit presented decreased juice content and TI values whereas did not appear significant effect on weight loss, SSC, TA and RI. Additionally, the use of 1-MCP has led to less attractive fruit to consumers, who tend to buy lemons in bright yellow color, due to its action on color index. Moreover, it did not manage to restrict the negative effects of degreening and the use of low temperature required as quarantine measurement, such as the postharvest decay and chilling injury.
Keywords: Lemons; Ethylene; 1-methylcyclopropene; Postharvest behavior; Λεμόνια; Αιθυλένιο; 1-μεθυλοκυκλοπροπενίου; Μετασυλλεκτική συμπεριφορά